PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT TANAMAN CABAI (Capsicum annuum L) DAN INTENSITAS SERANGAN LAYU FUSARIUM (Fusarium oxysporum Schlecth) PADA PEMBIBITANNYA: The effect of growing media on the growth and intensity of Fusarium wilt due to Fusarium oxysporum in chilli (Capsicum annum) nursery - Gunawan Djajakirana; Putri Handayani Sijabat (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2022)
Various fauna and flora live and thrive in the soil. The existence of soil organisms is not always beneficial for plant growth. Fusarium oxysporum is one of harmful fungi for plants that is living in soils. Plants affected by Fusarium oxysporum can show wilt symptoms and even die so that it becomes a limiting factor that causes decrease in production and crop failure. Several studies have been conducted to overcome the problem of Fusarium wilt in plants like eradicating disease-struck plants, using fungicides and using biological agents such as Trichoderma sp., but the Fusarium wilt disease can not be handled well. Based on this case, this research was conducted to determine the effective way to treat Fusarium wilt disease in chilli plants by improving the nursery media. This research was conducted by combining charcoal and or cocopeat with soil in which Fusarium had been developed. This is expected to improve the physical, chemical, and biological properties of the soil so that the growth of chilli seedlings will be better and the Fusarium oxysporum fungi does not infect chilli seedlings. The study was conducted in a plastic house using Completely Randomized Design (CRD). The results showed that the addition of charcoal and or cocopeat with soil show the significant effect on the growth of chili plants and decrease the level of disease intensity up to 0 % while the percentage of Fusarium wilt on soil only treatment reached 53.57 %. Based on this research, it was concluded that the addition of charcoal and or cocopeat media on soil media had a significant effect on the growth of chilli plants and inhibited the growth of Fusarium oxysporum even though the medium was infected with that fungi.